MANAJEMEN STRATEGY BLUE OCEAN PROGRAM BIMBINGAN DAN KONSELING ERA GLOBALIASI PADA SEKOLAH MENENGAH ATAS (SMA) - Sultani, Sultani; Mahfuz, Mahfuz (JURNAL KONSELING GUSJIGANG, 2017)
The purpose of this study is to know the impact of globalization on student behavior, management strategy guidance counseling and counseling create a value or value, planning an effective and efficient guidance and counseling program with innovative and covative bloe ocean strategy approach by guidance and counseling teachers. Creating a competitive person. Qualitative Descriptive research method with primary data source is teacher guidance and counseling in 4 person. The results of Globalization research have an impact on the behavior of learners both existing and non adaftif.Perencanaan guidance and counseling programs are effective and efficient with the approach of blue ocean strategy in designing the program semester, monthly and daily as well as the agenda of continuous changes or innovations and criatif by teachers guidance and counseling in terms of value needs or value for learners as a coustumer service primery that sesaui results need assessment. So as to create polite behavior and spirit to perform.